Penerapan Metode an-Nashr untuk Meningkatkan Daya Ingat dan Kemampuan Menterjemah Siswa di MTs Babul Futuh Pandaan - Muhlis, Muhammad (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
Islamic religious education which is the main basis or main source is the holy book of the Al-Qur'an. Al-Qur'an is the word of Allah that was sent down to the prophet Muhammad SAW through the intermediary Ruhul Amin (Angel Jibril) and it is narrated to us by way of tawatur (continuous) which is from worship because of reading it. Starting with the letter Al-Fatihah and ending with the letter An-Nas. By just reading it, we have served Allah and get a reward. But the best among us are those who study it and teach it to others. The type used in this research is descriptive research with a qualitative research method approach. In descriptive research that uses a qualitative research approach, the research report will contain data quotations to provide an overview of the report presentation. MTs Babul Futuh Pandaan is one of the institutions that applies Christian teaching to students in order to improve their memory and ability to translate verses of the Al-Qur'an. Using the An-Nasr method will make it easier for students to memorize the Al-Qur'an and its translation properly. The teaching and learning application of the An-Nashr method at MTs Babul Futuh pandaan uses a 3-2-1 pattern